A Green Method for Synthesis of Silver-Nanoparticles-Diatomite (AgNPs-D) Composite from Pineapple (Ananas comosus) Leaf Extract - Saprini Hamdiani; Yeng-Fong Shih (Indonesian Journal of Chemistry, 2021)
This study aims to develop a green method to load silver nanoparticles (AgNPs) into the diatomite (D) pores to produce AgNPs-D composite material. The AgNPs were synthesized by pineapple leaf extract at the temperature of 70 °C for 30 min. The composite formation was characterized by UV-Vis, FTIR, TGA, particle sizes analysis, gravimetric, and color observation. The appearance of surface plasmon bands in 440–460 nm confirms the AgNPs formation. The percentage of the AgNO3 which converted to AgNPs was 99.8%. The smallest particle size of AgNPs was 30 nm, obtained in an AgNO3 concentration of 1 mM with a stirring time of 24 h at 70 °C. The colloidal AgNPs were stable for up to 7 days. The adsorption process of AgNPs was marked by the appearance of –C=O and –C–O– groups peak at 1740 and 1366 cm–1 on the FTIR spectrum. By adsorption and gravimetric technique, as much as 1 wt.% of AgNPs were loaded into D pores. The color of diatomite material changes from white to reddish-brown. The TGA analysis showed that the remaining D and AgNPs-D at 580 °C are 98.22% and 95.74%, respectively. The AgNPs loading through the green technology technique was expected to increase diatomite application in the biomedical field.